LOCAL WISDOM OF â€œMALAMANG AND MANJALANG MINTUOâ€ IN THE PERSPECTIVES OF CULTURE, SOCIAL, AND RELIGION IN MINANGKABAU WEST SUMATERA - Yusutria Yusutria (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
The tradition of â€œMalamang and Manjalang Mintuoâ€ is a tradition in Minangkabau, West Sumatra. The tradition has beenshifted with the changing times and began to be abandoned by youngers generation due to the influence of modernization. While the tradition initially has cul- tural and religious values contained in it based on cultural, social and religious life perspectives. The goals of cultural, social, and religious values are contained. As for the results of this research, it is found that values which are contained in cultural, social, and religious perspectives are historical cultural preservation due to the spread of Islam and a teaching to always do good thing such as charity; the building of friendship rela- tion among the societies; the introduction of halal food and teaching to have a great communication adjusted with the place and interlocutor; and give thanks and for wishing of blessing and salvation from God.